Skeletal Muscle Necrosis and Regeneration after Injection of BaH1, A Hemorrhagic Metalloproteinase Isolated from the Venom of the Snake Bothrops asper (Terciopelo) - Gutiérrez, José María (1995)
The effects of BaH1, a hemorrhagic metalloproteinase isolated from Bothrops asper venom, on mouse gastrocnemius muscle was investigated. The toxin induced severe hemorrhage within minutes after injection. Groups of necrotic muscle fibers were observed after the sixth hour, with evident disorganization of myofibrillar material. At the ultrastructural level myofibrils in these cells lost their regular arrangement, Z lines were absent, and sarcomeres were disoriented, although there was no evidence of myofilament clumping or hypercontraction. Plasma membrane was interrupted in many portions. Mitochondrial alterations included swelling and the formation of flocculent densities and dense intracristal plates. At 12, 24, and 48 hr necrotic cells had amorphous masses of myofilaments and abundant phagocytic cells were observed both within necrotic fibers and in the interstitial space. Fraction D-1, which contains the three hemorrhagic metalloproteinases BaH1, BH2, and BH3, did not cause direct muscle damage when incubated with gastrocnemius muscle in vitro. Upon intramuscular injection in mice this fraction induced a small but significant increment in muscle lactic acid levels. Observations carried out 7 and 14 days after BaH1 injection revealed some regenerating muscle fibers with centrally located nuclei. However, other areas had few regenerating fibers of reduced diameter, surrounded by abundant fibroblasts, fibrosis, calcification, and remnants of necrotic muscle cells. When BaH1 was injected together with B. asper myotoxin III, a myotoxic phospholipase A2 that induces myonecrosis but does not affect blood vessels, a poor muscle regeneration was observed. In contrast, if B. asper myotoxin III was injected alone, regeneration proceeded normally and successfully.